2017
DOI: 10.4172/2090-7214.1000258
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning Service Utilization and Its Associated Factors among Married Women in Benchi-Maji Zone, Southwest, Ethiopia: Community-Based Crosssectional Study

Abstract: In Ethiopia, contraceptive use has doubled in the last five years, but women still bears an average of five children and 25% of married women want to space or limit their births but are not currently using contraception. So that, the purpose of this study was to assess Family planning services utilization and its associated factors among married women in Benchi-Maji Zone, Southwest, Ethiopia.A community based cross sectional study was carried out to collect data from 801 randomly selected married women in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…According to this study having fewer children was associated with FP service utilization which is in contrary to the study done in Addis Ababa [23]. In this study history of induced abortion was not associated with FP utilization which is consistent with the study from southern Ethiopia [22,38]. The other factor inversely associated with FP utilization was intention to have children in the future which is consistent with other studies in Addis Ababa [13].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to this study having fewer children was associated with FP service utilization which is in contrary to the study done in Addis Ababa [23]. In this study history of induced abortion was not associated with FP utilization which is consistent with the study from southern Ethiopia [22,38]. The other factor inversely associated with FP utilization was intention to have children in the future which is consistent with other studies in Addis Ababa [13].…”
Section: Discussionsupporting
confidence: 84%
“…Factors that were shown to be associated with FP utilization in previous studies in Ethiopia such as, age, education, marital status, income and occupation of women were not associated with FP utilization in this study [17,18,30,38]. This may indicate that factors that affect FP utilization in such a vulnerable population as women with mental illness could be different from the general population.…”
Section: Discussioncontrasting
confidence: 57%
“…On the contrary, our finding was slightly higher than the studies in Southern (62.6%) [ 30 ], Central (62.1%) [ 38 ], and Northwestern (58.7%) [ 19 ] parts of Ethiopia. Besides, this findings was considerably higher than the result of the studies in Southwestern (17.4%) [ 17 ], and Southern (36.6%) [ 20 ] Ethiopia, Bangladesh (37.6%) [ 39 ], Zambia (40%) [ 40 ], India (46.4%) [ 41 ], and Qatar (52.2%) [ 42 ]. These discrepancies might be due to differences in the accessibility and availability of contraceptives and health facilities in the study areas.…”
Section: Discussionmentioning
confidence: 59%
“…In Ethiopia, although different studies have been conducted to determine the predictors of non-use of contraceptives among women, some of them were limited to the specific geographical areas and used relatively a small sample size [ 14 , 17 , 20 , 25 , 26 , 30 32 ]. In addition, these studies did not consider some community-level factors like region, residence, cluster, women illiteracy status, women’s non-exposure to mass media status.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, it contrasts with the study of, where the modal age was found to be 30-39 years. 20,21 Likewise, the highest proportions of the respondents were Christians. This finding is similar to the study conducted by, where most respondents were Christians.…”
Section: Discussionmentioning
confidence: 97%